Motivational Interviewing to Encourage Quit Attempts Among Smokers Not Ready to Quit: A Trial-Based Economic Analysis - Rasu, Rafia S (Nicotine Tob Res, 2019)
INTRODUCTION: This study used data from a randomized controlled trial evaluating the efficacy of motivational interviewing (MI) relative to health education (HE) and brief advice (BA) to encourage quit attempts and cessation in order to determine their relative cost-effectiveness. AIMS AND METHODS: Urban community residents (n = 255) with low desire to quit smoking were randomized to MI, HE, or BA which differed in communication style and/or number of treatment sessions. Incremental cost-effectiveness ratios were used to compare the intensive interventions (MI and HE) to BA for facilitating quit attempts and smoking cessation. Costs were calculated from the perspective of an agency that might engage in program delivery. Sensitivity analysis examined different assumptions for MI training and pharmacotherapy costs. RESULTS: Total intervention delivery time costs per participant for MI, HE, and BA were $46.63, $42.87, and $2.4, respectively. Cost-effectiveness ratios per quit attempt at 24 weeks were $380 for MI, $272 for HE, and $209 for BA. The cost per additional quit attempt for MI and HE relative to BA was $508 and $301, respectively. The cost per additional quit for MI and HE relative to BA was $2030 and $752, respectively. Four separate sensitivity analyses conducted in our study did not change the conclusion the HE had a lower Incremental Cost-Effectiveness Ratio for both quit attempts and cessation. CONCLUSIONS: HE was the most cost-effective of the three types of smoking cessation induction therapies and therefore may be preferable for smokers who are less motivated to quit. Providing valuable cost information in choosing different clinical methods for motivating smokers to quit. IMPLICATIONS: All direct costs and activity-based time costs associated with delivering the intervention were analyzed from the perspective of an agency that may wish to replicate these strategies. A randomized controlled trial evaluating the efficacy of MI relative to HE and BA to encourage quit attempts and cessation determined their relative cost-effectiveness. HE was the most cost-effective of the three types of smoking cessation induction therapies and therefore may be preferable. Despite guideline recommendations, MI may not be the best approach to encourage quit attempts in diverse populations. Rather, a structured, intensive HE intervention might be the most cost-effective alternative.